Clinical use of the Onclarity test with extended HPV genotyping and phenotyping in patients with suspected squamous intraepithelial lesions - Pruski, Dominik; Millert-Kalinska, Sonja; Klemenska, Paula; Jach, Robert; Przybylski, Marcin (Ginekologia polska, 2024)
Human papillomavirus (HPV) is the most widespread virus with oncogenic potential that infects humans and there is a need to look for the most effective screening method among the population. Understanding the role of HPV in cervical dysplasia and viruses typing increased the usage of HPV-based cervical cancer screening tests using genotyping. We aim to assess the usefulness the Onclarity Test with extended genotyping and phenotyping of HPV in detecting cervical squamous intraepithelial lesions in 695 subjects who registered for regular cervical screening or due to abnormal LBC result or positive HPV results. Incidence of positive HPV depended significantly on biopsy outcome (p < 0.001). It was the highest for patients with HSIL (92.5%), lower for patients with LSIL (57.9%) and with HPV outcome of biopsy (50.0%). The sensitivity of positive HPV for detecting HSIL was equal to 92.50% (95% CI: 79.61%-98.43%), and specificity equalled 55.26% (95% CI: 43.41-66.69%). Sensitivity of HPV positive for any of 16, 18, 31, 45, 51 or 52 genotypes but not belonging to the P1, P2 or P3 group for detecting HSIL equalled 62.50% (95% CI: 45.80-77.27%), specificity equalled 72.37% (95% CI: 60.91-82.01%). The Onclarity test is characterised by high sensitivity and specificity in detecting CIN2+ lesions. Extended genotyping enables the identification of the most common oncogenic HPV types in the population. It can be used as a basic tool for secondary prevention or together with LBC.